Digestive flexibility in response to environmental salinity and temperature in the non-symbiotic sea anemone Bunodosoma zamponii - del Valle, Juana Cristina (2015)
In spite of their ecological importance in tidal pools, studies on digestive flexibility in non-symbiotic anemones (i.e., without symbiosis throughout their life) upon changes in key environmental factors are lacking. This study constitutes the first work to investigate the response of digestive enzymes in relation to high environmental salinity and temperature in a non-symbiotic sea anemone. We determined the occurrence and biochemical characteristics of maltase activity and compared maltase and proteolytic activities in mesenterial filaments in Bunodosoma zamponii from the intertidal area of Punta Cantera, Mar del Plata, Argentina (38°05′S, 57°32′W) acclimated to 35 and 40 psu and after an acute enhancement (15 min) of temperature from 20° to 30°C. Maltase activity was higher in 40 psu and upon the increase in temperature (about 80 and 99%, respectively). Proteolytic activity was not affected in any case. The results suggest the occurrence of specific digestive adjustments in relation to high salinity and temperature. The fact that differential modulation of maltase activity could be associated with a higher digestive capacity for glycogenic substrates is discussed.